EFFICACY OF ZINC AS ADJUNCT THERAPY IN CHILDHOOD PNEUMONIAADMITTED IN A TERTIARY CARE HOSPITAL (The Research of Medical Science Review, 2025)
Background: Pneumonia is a leading cause of morbidity and mortality in children, particularly in developing countries. Zinc, known for its immune-modulating properties, has been suggested as an adjunct therapy to improve recovery outcomes in childhood pneumonia. Objective: To evaluate the efficacy of zinc supplementation as an adjunct therapy in reducing recovery time and hospital stay in children with pneumonia. Study Design and Setting: This randomized, double-blind, placebo-controlled trial was conducted at Department of Paediatrics Sughra Shafi Medical Complex, Narowal over duration of 6 months from 14 November 2022 to 14 May 2022. Methods: Total 128 children aged 2 months to 5 years, diagnosed with pneumonia were included. Participants were randomly assigned to receive either zinc supplementation (n=64) or placebo (n=64), alongside standard antibiotic treatment. The zinc group received zinc sulfate (20 mg/day for children over 12 months and 10 mg/day for infants) for 7-10 days. Primary outcomes were time to clinical recovery, duration of hospital stay, and need for second or third-line treatments. Secondary outcomes included respiratory rate, oxygen saturation, and laboratory findings such as hemoglobin levels and serum zinc levels. Data were analyzed using appropriate statistical tests, with p-values <0.05 considered significant. Results: The zinc group had a significantly shorter recovery time (64.6 ± 8.51 hours) compared to the placebo group (82.5 ± 9.55 hours, p < 0.001). The duration of hospital stay was also shorter in the zinc group (72.7 ± 6.99 hours 89.2 ± 10.84 hours, p < 0.001). No significant differences were observed in treatment failure rates. Conclusion: Zinc supplementation significantly improves recovery time and reduces hospital stay in children with pneumonia, supporting its role as an effective adjunct therapy.